Humanization with the family in an intensive care unit: a descriptive study - Vedootto, Denise de Oliveira; Silva, Rosângela Marion da (Online Brazilian Journal of Nursing, 2011)
The progress in technology offered a lot of benefits and advances in the way health care is provided, but the aspects of human care are very difficult to be practiced and implemented in that sector. The process of the humanization perceived by family members of patients hospitalized in the Intensive Unit Care was analyzed and identified in order to create a relationship . It is a descriptive and exploratory research , with a qualitative approach. The research was realized in a University Hospital located in Rio Grande do Sul with patients’ families that were select aleatory to participate in a interview. The data was analyzed in the following categories: The way health care was offered, The integration between nurses and doctors, and the process of humanization allied in those families’ experiences. It is necessary to revise values, open up for discussion and questions in order to facilitate the implementation of processes of humanization to understand the necessities of the patients’ families.